Increasing Vocabulary Mastery Through Storytelling For The Fifth Year Students Of SD Negeri 1 Gondang In 2011/2012 Academic Year - Hidayati, Puji, Drs. Djoko Srijono, M.Hum, Dr. Anam Sutopo, M.Hum (2013)
This research aims at knowing whether or not the implementation of storytelling method increases vocabulary for the fifth year students of SD Negeri 1 Gondang and describing the implementation of teaching vocabulary by storytelling to increase vocabulary mastery for the fifth year students of SD Negeri 1 Gondang. The action research was conducted in the fifth year of SD Negeri 1 Gondang. The writer taught vocabulary using storytelling. There were two cycles of action, each cycle consisted of planning, implementing, observing, and reflecting. In this research, the data are derived from used event, respondent, and document. There are three methods of collecting data namely: observation, interview, and content analysis. The result of the study shows that after the writer conducted the action, the students' vocabulary mastery is higher than before. It can be seen from the result of both the observation of the students' activities during the action and the mean of written and oral test in every action. Meanwhile, to find the significant difference between the students' achievement before and after action, she used the nonindependent t-test. The result shows that the t-observation is always greater than the t-table in degrees of freedom N-1 and level of significance 0,05. It means that there is a significant difference of students' achievement before and after action. So, it can be concluded that teaching vocabulary though storytelling can increase the students' vocabulary mastery.